2022
DOI: 10.3390/math11010024
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis and DSP Implementation of Memristor Chaotic Systems with Multiple Forms of Hidden Attractors

Abstract: In this paper, a new six dimensional memristor chaotic system is designed by combining the chaotic system with a memristor. By analyzing the phase diagram of the chaotic attractors, eleven different attractors are found, including a multi-wing attractor and symmetric attractors. By analyzing the equilibrium point of the system, it is proven that the system has the property of a hidden chaotic attractor. The dynamic behavior of the system when the three parameters change is analyzed by means of LEs and a Bifurc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In this case, the attractor around O(0, 0) at ˆ0.36 c = is enlarged, and the BA of the higher amplitude attractor around O(0, 0) at ˆ0.37 c = is fur- When f 0 increases to 0.007, bistability around each nontrivial center also appears in system (4) at ĉ = 0.36 and ĉ = 0.37 (see Figure 9(c-1,c-2)). Even though the new attractors are of much higher amplitudes, their BAs are so small and fractal that they are called rare and hidden attractors [32][33][34]. Accordingly, it is almost impossible for system (3) to achieve these attractors.…”
Section: Coexisting Responses and Their Bas At ω = 07mentioning
confidence: 99%
“…In this case, the attractor around O(0, 0) at ˆ0.36 c = is enlarged, and the BA of the higher amplitude attractor around O(0, 0) at ˆ0.37 c = is fur- When f 0 increases to 0.007, bistability around each nontrivial center also appears in system (4) at ĉ = 0.36 and ĉ = 0.37 (see Figure 9(c-1,c-2)). Even though the new attractors are of much higher amplitudes, their BAs are so small and fractal that they are called rare and hidden attractors [32][33][34]. Accordingly, it is almost impossible for system (3) to achieve these attractors.…”
Section: Coexisting Responses and Their Bas At ω = 07mentioning
confidence: 99%
“…On the other hand, Li et al introduced a memristor into a jerk system and proposed a four-dimensional memristive chaotic system, which exhibits rich dynamical behaviors including extreme multi-stability and offset boosting [17]. Guo et al integrated a memristor with a chaotic system and devised a novel six-dimensional memristive chaotic system, in which they observed phenomena such as chaotic degeneration, coexistence of multiple attractors, and offset boosting [18]. Zeng et al proposed a special memristor-based Jerk system, which found the sensitivity of the initial state of the system and generated complex behaviors such as multi-stablestates [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to formula(18) and(19), we get thatC 1 = C 2 = C 3 = C 4 = 1 uF, R 11 = R 14 = 10 kΩ, R 7 = 45.5 kΩ, R 6 = 6.25 kΩ, R 10 = 100 Ω, R 8 = 1.428 kΩ, R 15 = 3.33 kΩ, R 26 = 1 MΩ, R 21 = 560 Ω. In the part of the circuit of the tanh, R 1 = R 3 = R 4 =1 kΩ, R 13 = R 16 = R 17 = R 18 = R 12 =10 kΩ, R 2 = 520 Ω, R 5 = 7.2 kΩ, R 9 = 11.646 k.…”
mentioning
confidence: 99%
“…However, it was not until 2008 that HP Labs made a solid-state memristor, [8] which marks that the research on memristors has officially changed from theory to practice. With the deepening of the research on memristors, [9,10] the special nonlinearity and nonvolatility of memristors have made them widely used in chaos, [11][12][13] neural networks, [14][15][16][17][18][19][20] secure communication, [21,22] memory, [23] neurons, [24] and chaotic oscillators. [25,26] More and more researchers have found that adding memristors to chaotic circuits will greatly increase the complexity of the system and cause some other behaviors in the chaotic system.…”
Section: Introductionmentioning
confidence: 99%